A qualitative analysis of college students’ interest in mHealth solutions - Hoglund, Leslie; Becker, Craig M.; Tonn, Cara (Frontiers in Public Health, 2025)
This study explores college students’ perceptions of an AI-driven mHealth application designed to promote well-being. With rising mental health challenges in academic settings, students increasingly seek digital tools that provide holistic support for physical, mental, and financial health. Through focus groups, this qualitative study examines students’ preferences for personalized health tracking, educational content, and flexible reminders within a private, supportive community. Key findings emphasize students’ desire for a balanced, all-in-one app that integrates health and wellness tools without overwhelming them with notifications. Students also highlighted the importance of social media integration for outreach, though concerns were raised about potential stress from competitive online environments. The findings underscore the value of user-centered design in developing mHealth solutions that foster engagement, simplify wellness management, and respect user privacy. This research contributes to understanding how digital platforms can be tailored to support college students’ well-being effectively.